2007
DOI: 10.1128/jvi.02748-06
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Human Cytomegalovirus Receptors in Cytotrophoblasts Correlates with Distinct Replication Sites in the Placenta

Abstract: Cytomegalovirus (CMV), the major viral cause of congenital disease, infects the uterus and developing placenta and spreads to the fetus throughout gestation. Virus replicates in invasive cytotrophoblasts in the decidua, and maternal immunoglobulin G (IgG)-CMV virion complexes, which are transcytosed by the neonatal Fc receptor across syncytiotrophoblasts, infect underlying cytotrophoblasts in chorionic villi. Immunity is central to protection of the placenta-fetal unit: infection can occur when IgG has a low n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 65 publications
6
65
0
Order By: Relevance
“…qRT-PCR analysis confirmed EGFR-mediated viral entry (Fig. 2G) and revealed a 41% and 59% decrease in viral entry in the presence of neutralizing-EGFR antibody and AG1478, respectively, which is consistent with the 63% reduction in infectivity observed in trophoblasts treated with an anti-EGFR antibody before HCMV infection (11). Other growth factor-like receptor tyrosine kinases, including PDGFR-␣, VEGF receptor 1 (VEGFR1), and VEGFR2, are not involved in mediating viral entry into monocytes (Fig.…”
Section: Hcmv-induced Egfr Engagement and Activation Are Required Forsupporting
confidence: 80%
See 4 more Smart Citations
“…qRT-PCR analysis confirmed EGFR-mediated viral entry (Fig. 2G) and revealed a 41% and 59% decrease in viral entry in the presence of neutralizing-EGFR antibody and AG1478, respectively, which is consistent with the 63% reduction in infectivity observed in trophoblasts treated with an anti-EGFR antibody before HCMV infection (11). Other growth factor-like receptor tyrosine kinases, including PDGFR-␣, VEGF receptor 1 (VEGFR1), and VEGFR2, are not involved in mediating viral entry into monocytes (Fig.…”
Section: Hcmv-induced Egfr Engagement and Activation Are Required Forsupporting
confidence: 80%
“…Several studies have reported the rapid activation of EGFR to occur in various cell lines following HCMV infection (8)(9)(10) and that the activation of EGFR signaling was required for efficient infection (8,11). We similarly found that EGFR activity was necessary for HCMV entry into primary monocytes, although in contrast to model cell types (23), activation of the downstream target PI(3)K was not required for HCMV entry.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations